(untitled) (Muitas Vozes, 2024)
This paper is dedicated to present an approach between literature and other arts, more specifically between the poetry of Conceição Evaristo and the paintings of Titus Kaphar. We focus our analysis on the poems "Vozes-mulheres" and "Certidão de óbito" by the Brazilian poet, and the paintings "A space to forget" and "From a tropical space" by the American painter. For this purpose, we conduct an analytical gesture from an exilic perspective, which we recognize as representing the condition of black individuals in American territories, strongly marked in the works of Conceição Evaristo and Kaphar, in a tone of denunciation. The analysis is supported by the studies of Said (2002), Nancy (1996), Pacheco (2022), Kilomba (2019), and Pollak (1992).